2002
DOI: 10.1046/j.1341-8076.2002.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study comparing retroperitoneal drainage with no drainage and no peritonization following radical hysterectomy and pelvic lymphadenectomy for invasive cervical cancer

Abstract: Routine retroperitoneal drainage and peritonization after RHPL for invasive cervical cancer can be safely omitted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
9
0
5
Order By: Relevance
“…Previous studies reported that drain following retroperitoneal lymphadenectomy could not reduced postoperative lymphocysts and morbidities. 17,18 The insertion and management of drain after retroperitoneal lymphadenectomy need further study. After excluding urinary injury and other causes authors planed to treat the patient as in chylous ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that drain following retroperitoneal lymphadenectomy could not reduced postoperative lymphocysts and morbidities. 17,18 The insertion and management of drain after retroperitoneal lymphadenectomy need further study. After excluding urinary injury and other causes authors planed to treat the patient as in chylous ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Une mé ta-analyse ré cente de la Cochrane Database [44], comprenant quatre é tudes randomisé es et 571 patientes, a montré que l'utilisation de drains pelviens en cas de CP ne pré venait pas la survenue de lymphocè le voire augmentait le risque [11,12,30,45]. Le pé ritoine é tait laissé ouvert dans trois é tudes [11,30,45].…”
Section: Drainagesunclassified
“…Le pé ritoine é tait laissé ouvert dans trois é tudes [11,30,45]. Dans l'é tude de Srisomboon, le pé ritoine é tait fermé dans le groupe avec drainage [12]. Le taux de lymphocè le postopé ratoire é tait comparable avec ou sans drainage quatre semaines aprè s la chirurgie.…”
Section: Drainagesunclassified
See 1 more Smart Citation
“…Pelvic suction drainage following lymph node dissection had formerly been used to prevent the occurrence of pelvic lymphocyst. However, it was found that the incidence of this complication was the same whether patients underwent retroperitoneal drainage or not [8][9][10][11] , and that it might occur even more frequently in patients who underwent this procedure [12] .…”
Section: Introductionmentioning
confidence: 97%